Recording of a volume transmitting vortex hologram in a photorefractive crystal of bismuth silicate - Zhao, Xie; Dadenkov, Ivan G.; Melnikova, Elena A.; Tolstik, Alexei L. (Journal of the Belarusian State University. Physics, 2024)
Recent breakthroughs in vortex beam research, characterised by structured beams bearing orbital angular momentum, have significantlytransformed various applications of beams. These advancements have notably impacted fieldssuch as advanced optical manipulation, high capacity optical communications, and super-resolution imaging. Undoubtedly, the development and refinementof generation and detection techniques for vortex beams play pivotal roles in enabling and enhancing their applications. In this work, pulsed recording of dynamic holograms of singular beams in photorefractive bismuth silicate crystals is realised. The experimental setup presented in this work is based on the recor ding of transmissive volume dynamic holograms, which allows us to use a wide spectral range to reconstruct the holo graphic image. A volumetric static hologram recorded in a photopolymer layer was used as a singular beam source. The restoration of the recorded hologram was realised using a continuous laser with a differentwavelength, which allowed the recording and restoring beams to be spatially separated. An interference method for determining the topological charge of an optical vortex from the transmitted and restored beams was also realised.
Keywords: holography; photorefractive crystals; optical vortices; bismuth silicate; interference pattern